Extraction and characterization of gelatine from chicken skin - Robiatun Ain, Maidin (2013)
Gelatine is mixture of peptides and protein produce by partial hydrolysis of collagen from the animal skin, connective tissue and bones. Gelatine has gelling, foaming and emulsifying properties that contribute to a wide range of applications in the food, pharmaceutical, photographic and cosmetic industries. In the current study, gelatine was extracted from the chicken skin and was characterized in term of yield, molecular weight, melting point and viscosity. Two different pre-treatment methods using acetic acid and nitric acid were used during preparation of gelatine. The yield of gelatine using acetic acid and nitric acid pre-treatment are 11.19 %(w/w) and 9.18%(w/w) respectively based on dry weight basis. Both gelatines showed the same molecular weight pattern range from 53 to 250 kDa. The viscosity of gelatine using acetic acid and nitric acid pre-treatment are 3.3 mPa.s and 2.8 mPa.s respectively